Corporate Social Responsibility and the Three Sectors in Asia : How Conscious Engagement Can Benefit Civil Society - Hasan, Samiul (Springer New York : Imprint: Springer, 2017)
This volume investigates how much governmental control is needed to reign in corporate and business greed and to make business "socially responsible" in Asia. It also questions whether business entities need to be reigned in by the government itself, or if other social, religious, or economic dynamics shape business entities in Asia. Moreover, it looks at how the Asian third sector influences BSR/CSR activities.
Keywords: Social sciences.; Culture -- Study and teaching.; Business ethics.; Social policy.; Sociology.; elektronické knihy; electronic books